Advances in mergers and acquisitions. vol. 21 - Cooper, Cary L.; Finkelstein, Sydney (Advances in mergers and acquisitions ;, 2022)
Advances in Mergers and Acquisitions stands out from the competition due to its focus on three key characteristics: studies from scholars in different countries, with different research questions, relying on different theoretical perspective. Such a broad and inclusive approach to mergers and acquisitions is not easily replicated in academic journals, with much narrower mandates and metrics. Volume 21 of this annual series explores a range of issues relevant to a post-Covid world and the ensuing recession - from the perks and pitfalls of cross-legacy boundary-spanning and the role of inimical resources in managerial decisions, to the synergy between industry 4.0 and the circular economy and the role of M&A advisors in cross-border acquisitions, the chapters published in this volume provide cutting edge ideas by leading scholars and help to inform mergers and acquisitions research around the world. This collection of research is of interest to scholars in strategic management, organization theory, and organizational behaviour who are studying questions around mergers and acquisitions. Doctoral students in particular will benefit from access to the diversity of research that can trigger new research questions and expanded research agendas.